Permasalahan Regulasi Penanganan Dumping di Indonesia dan Potensi Praktik Persaingan Tidak Sehat Melalui Upaya Anti-Dumping - Sarah Amalia Nursani (Jurnal Interpretasi Hukum, 2024)
International trade is one activity that is inevitable. Through international trade, a country's economic growth has the possibility to grow faster, opening up opportunities to attract investors into Indonesia which will then have the opportunity to create jobs and reduce unemployment in Indonesia. However, despite its positive impact, international trade has problems that can be a double-edged sword. One of them is the application of anti-dumping policies to prevent dumping, which raises the potential for unfair business competition practices and makes the quality of Indonesian products unable to compete because it opens the potential for domestic companies to take advantage of the policy. Moreover, dumping is not a difficult practice to prove considering the number of anti-dumping measures that have been counter-sued by countries suspected of dumping. The research method that will be used to analyze these matters is the doctrinal legal research method to examine the regulations in Indonesia governing dumping including examining some of the weaknesses of the application of these rules.